The Camouflage of “Tough Woman”: The Resistance of Female Character Against Patriarchal Ideology in Mulan - Lailawati, Rahmadani; Hutahaean, Sorta; Islami, Qori; Nursafira, Mutia Sari (Universitas Lancang Kuning, 2020)
This present study exposes how the patriarchal ideology still survives in the international English movie depicting Chinese women, Mulan (1998) and Mulan (2020). This present study uses critical discourse analysis to analyse the movies, focusing on the the dialogue, characteristics and events in the movies. This study contributes by critically comparing how English movies which are directed and scripted by English native speakers depict the role of women in the patriarchal China. The results showed that despite the 22-year gap between movies, the portrayal of women becomes worse, presented differently due to a change in genre, and is only seemingly improved at the tail end of the latest movie. While there are differences in how both Mulans are faced with problems and how they face said problems, her resistance as female neither reflects nor felt by Chinese women.